Efecto de la Hidratación en el cambio de Volumen y contenido de Humedad de granos de frijol Garbancillo (Phaseolus vulgaris L) - Vela Valderrama, Nory Elisa (2019)
This research work determined the effect of hydration on the change in volume and moisture content of dried chickpea bean beans (Phaseolus vulgaris L), is intended to help improve and recognize the hydration characteristics of the grains for subsequent benefit, for which it has been proposed to contribute to optimize time and money, since depending on the grain to be used, the best model to work will be set. The sphericity factor (length, width and height) of 20 bean grains was evaluated with the ImagJ program, which studied 4 models (Aschenbrenner; Wadell; Aguerre, Gabito, Chirife and Mohsenin, 1970) getting to fit the Wadell model with a sphericity factor of 0.843. The change of mass was studied due to the change of volume in beans at temperatures of 20, 27, 37 and 47 ° C, with 20 times and 3 repetitions at each temperature, 6 hydration models were used (Peleg, Weibull, Page, Ibarz-Augusto, Gompertz and Kaptso) the models that fit in reference to the MSD, RMSD and NRMSD are Peleg and Weibull modeling concavely. Temperature models were also evaluated (Arrhenius Equation, Exponential Equation, Empirical Equation 1 referring to the volume of the model that fits; it is the Empirical Equation 1 and 2 with the Peleg model; evaluating the MSD, R2 and b.